Trapezius Tear Causing Scapular Winging Treated with Rhomboid Transfer and Achilles Allograft Reconstruction: A Case Report. Issue 2 (April 2021) - Tang, Peter; Schreck, Mark
Abstract : Case: This is a case of an 18-year-old woman with superior and lateral scapular winging due to traumatic injuries to the insertions of the superior and middle trapezius as well as the origins of the latissimus dorsi and lower trapezius. Conclusion: Scapular winging can be caused by a muscle tear in absence of a nerve injury. This patient underwent latissimus dorsi origin repair and superior and middle trapezius repairs. An Achilles allograft was used to reconstruct her lower trapezius to provide static restraint to her scapula, while a rhomboid major transfer was performed to provide dynamic restraint.